Analysis Kurikulum Merdeka in The Perspective of Humanistic Learning Theory - Aiman, Ummu; Lasmawan, I Wayan; Suastra, I Wayan (Jurnal Ilmiah Profesi Pendidikan, 2024)
The main focus of this research is related to the study of educational concepts from the perspective of humanistic learning theory in the independent learning curriculum. The type of research used is library research which is taken from several literatures including notes, books, articles, journals and other scientific literature references. The independent curriculum can be viewed and analyzed using educational concepts from the perspective of humanistic learning theory. In the Merdeka Curriculum, the concept of education from the perspective of humanistic learning theory plays an important role. Humanistic learning theory has the aim of humanizing humans. Learning in humanistic theory is said to be successful if students can understand the environment and themselves (achieve self-actualization). And in general, this humanistic theory is a learning theory that prioritizes the learning process, not the learning outcomes. This theory develops the concept of humanizing humans so that students are able to understand themselves and their environment. The process of implementing the independent curriculum in this research is discussed based on a humanistic approach, in accordance with the results of the taxonomy developed. So the results of the dimensions of the independent curriculum taxonomy in the humanistic learning theory approach that have been developed, then look for suitability with the curriculum implementation practices carried out.